(untitled) (Research, Society and Development, 2022)
The frequent and intense attacks that Science has been suffering disqualify it from society and, especially in the new coronavirus pandemic, promote denial discourse and (dis)infodemic, intensifying the importance and urgency of scientific dissemination, which can be carried out from of the execution of extension projects. Therefore, this study aim to evaluate the impact of two editions of an extension course on the quality of knowledge of the public served and their competence in confronting scientific denialism. The course took place in 2020, in two virtual editions, and had a total of 29 speakers and 382 subscribers, reaching 53 cities distributed in 17 Brazilian states, covering all geographic regions of Brazil. Among the themes addressed were the relationship between the virus and the environment, the means of contagion and prevention methods, socioeconomic, historical-geographic and educational issues. Approximately 40% of course participants had some belief demystified and 95% became multipliers of the information obtained by talking to someone about what they were learning in the course, which highlights the importance of carrying out extension actions as an effective tool to combat scientific denialism.